The effect of web interface features on consumer online purchase intentions - Maryam Masoudi; Fatemeh Shekarriz; Sorour Farokhi (Management Science Letters)
Information and communication technology plays essential role for people’s day-to-day business activities. People receive most of their knowledge by processing, recording and transferring necessary information through surfing Internet websites. Internet as an essential part of information technology (IT) has grown remarkably. Nowadays, there have been significant amount of efforts in Iran for developing e-commerce. This paper studies the effects of environmental internet features on internet purchase intention. The study divides internet environment into demographic and technologic parts and, for studying each of them, many features are investigated such as internet connection speed, connectivity model, web browser, type of payments, user’s income, user’s education, user’s gender, frequency of online usage per week and users’ goal for using internet. Using Logistic regression technique, the study has determined a meaningful effects of income, education, connection type, browser and goal on consumers’ behavior.